Advances in the Microbial Synthesis of 5-Hydroxytryptophan - Liu, Xin-Xin; Zhang, Bin; Ai, Lian-Zhong (Frontiers in Bioengineering and Biotechnology, 2021)
5-Hydroxytryptophan (5-HTP) plays an important role in the regulation of emotion, behavior, sleep, pain, body temperature, and other physiological functions. It is used in the treatment of depression, insomnia, migraine, and other diseases. Due to a lack of effective biosynthesis methods, 5-HTP is mainly obtained by natural extraction, which has been unable to meet the needs of the market. Through the directed evolution of enzymes and the introduction of substrate supply pathways, 5-HTP biosynthesis and yield increase have been realized. This review provides examples that illustrate the production mode of 5-HTP and the latest progress in microbial synthesis.